Molecular approach to find target(s) for oligoclonal bands in multiple sclerosis. Issue 1 (1st July 1998) - Rand, Kenneth H; Houck, Herbert; Denslow, Nancy D; Heilman, Kenneth M
Abstract : OBJECTIVES: Oligoclonal bands are a characteristic finding in the CSF of patients with multiple sclerosis, yet their target antigen(s) remain unknown. The objective was to determine whether a filamentous phage peptide library could be employed to allow the oligoclonal bands to select their own target epitopes. METHODS: CSF IgG antibody from 14 patients with multiple sclerosis and 14 controls was used to select individual phage clones from a bacteriophage library containing≈4 × 10 7 different hexamers expressed on its surface pIII protein. The amino acid sequence selected was deduced by sequencing the DNA of the genetically engineered insert. RESULTS: In general, after three rounds of selection, CSF from both patients with multiple sclerosis and controls selected one to two consistent peptide motifs. Five out of 14 patients with multiple sclerosis, and one control, selected the amino acid sequence motif, RRPFF. Given 20 possible amino acids per position, the likelihood of five patients selecting the same linear five amino acid sequence is at most 1.6 × 10 -13, corrected for the number of clones sequenced. A GenBank computer search showed that this sequence is found in the Epstein-Barr Virus nuclear antigen (EBNA-1), and a heat shock protein αB crystallin. Human serum antibodies to a synthetic peptide containing RRPFF were virtually exclusively found in patients with prior infection by Epstein-Barr virus. Other studies have suggested a relation between Epstein-Barr virus infection and multiple sclerosis, including nearly 100% Epstein-Barr virus seropositivity among patients with multiple sclerosis and increased concentrations of antibody to EBNA in CSF of patients with multiple sclerosis. By antigen specific immunoblotting, antibodies to the RRPFF motif in the CSF were shown to correspond to a subset of oligoclonal bands in the CSF from the same patient. CONCLUSION: This study shows that phage epitope display libraries may be used to select amino acid motifs which are potentially relevant to the pathogenesis of multiple sclerosis.